2013
DOI: 10.1111/cei.12017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interleukin-6 receptor blockade on the balance between regulatory T cells and T helper type 17 cells in rheumatoid arthritis patients

Abstract: Although no changes were detected in the frequency of Th1 or Th17 cells, the percentages of peripheral Tregs increased after therapy. In addition, the infrequent Th17/Th1 subpopulation showed a significant increment in tocilizumab-treated patients. In conclusion, tocilizumab was able to skew the balance between Th17 cells and Tregs towards a more protective status, which may contribute to the clinical improvement observed in RA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(76 citation statements)
references
References 22 publications
7
65
1
3
Order By: Relevance
“…In the case of RA, it has been shown that tocilizumab treatment led to improvement in systemic and joint inflammatory markers (Garnero et al 2010;Terpos et al 2011;Kanbe et al 2012), but it remained to be determined whether it can rectify fundamental immunological abnormalities, such as autoantibody production or imbalance of effector CD4 þ T-cell subsets (Tanaka 2013). However, recent preliminary results indicate that tocilizumab treatment can correct the imbalance between Th17 and Treg in peripheral blood CD4 þ T cells (Samson et al 2012;Pesce et al 2013). Moreover, it was shown that the treatment caused a reduction in the level of serum IgG4-class anticyclic citrullinated peptide Ab in RA (Carbone et al 2013).…”
Section: Il-6 In Inflammation Immunity and Diseasementioning
confidence: 99%
“…In the case of RA, it has been shown that tocilizumab treatment led to improvement in systemic and joint inflammatory markers (Garnero et al 2010;Terpos et al 2011;Kanbe et al 2012), but it remained to be determined whether it can rectify fundamental immunological abnormalities, such as autoantibody production or imbalance of effector CD4 þ T-cell subsets (Tanaka 2013). However, recent preliminary results indicate that tocilizumab treatment can correct the imbalance between Th17 and Treg in peripheral blood CD4 þ T cells (Samson et al 2012;Pesce et al 2013). Moreover, it was shown that the treatment caused a reduction in the level of serum IgG4-class anticyclic citrullinated peptide Ab in RA (Carbone et al 2013).…”
Section: Il-6 In Inflammation Immunity and Diseasementioning
confidence: 99%
“…1) [1,19]. Through this mechanism, TCZ decreases the circulating levels of neutrophils, neutrophil infiltration into inflamed joints [20], circulation of myeloid dendritic cells [21], monocyte levels, serum macrophage migration inhibitory factor levels [21,22], and levels of T helper 17 (Th17) cells, while increasing regulatory T cells [23,24]. TCZ also induces regulatory B-cell expansion, decreases B-cell hyperactivity, and decreases the number of peripheral memory B cells.…”
Section: Tocilizumab: the First Interleukin-6 Receptor-neutralizing Bmentioning
confidence: 99%
“…B. Pesce и соавт. [108] также вы-явили увеличение числа Т рег после 4 и 6 мес терапии ТЦЗ в группе из 8 пациентов с активным РА, но не отметили влияния препарата на содержание Th17-лимфоцитов. J. Kikuchi и соавт.…”
Section: ингибиторы рецепторов интерлейкинаunclassified